Fatigue Damage Map of AZ31B-F Magnesium Alloys under Multiaxial Loading Conditions - Vitor Anes; Luis Reis; Manuel Freitas (Metals, 2021)
In this work, the mechanical behavior of the AZ31B-F magnesium alloy under cyclic loading is analyzed with the goal of contributing to the advancement of its use in the design of AZ31B-F components and structures. To achieve this goal, an experimental program was implemented to evaluate the cyclic response of the AZ31B-F under specific proportional loads with different stress amplitude ratios. Afterwards, regression methods were applied to extend the experimental data to a wide range of proportional loads. As a result, the AZ31B-F damage map, a material property that stablishes the damage scale between normal and shear stresses for finite life loading regimes, was obtained. In addition, a safety factor was developed for the AZ31B-F material when subjected to proportional loading. The achieved results have a direct application in mechanical design of components/structures made of AZ31B-F contributing to its reliability.